Contractor Credit Handling Procedure At PT. BPR Bank Boyolali (PERSERODA) - Hafsha Hannunazza; Sutrisno, Sutrisno (International Journal of Economics, Business and Innovation Research, 2025)
Banks play an important role in economic growth. Economic growth must also be supported by the development of infrastructure in the region. Therefore, speed and accuracy are needed in development. In development, qualified human resources are needed, namely contractors who have adequate qualifications and capital. However, in reality there are still many contractors with these qualifications but do not have sufficient capital. Therefore, PT BPR Bank Boyolali (PERSERODA) facilitates this problem with the existence of Contractor Credit. This Contractor Credit is given to contractors who have met the requirements and are domiciled in Boyolali Regency. In providing Contractor Credit, it must meet certain aspects and existing procedures, and follow the established flow. This study contains the procedures for handling Contractor Credit at PT BPR Bank Boyolali (PERSERODA). This study aims to determine the handling of Contractor Credit, handling of problematic credit in Contractor Credit and the weaknesses of Contractor Credit. The results of this study are suggestions for overcoming the weaknesses of Contractor Credit.